Pengaruh Efektivitas Penerapan SIA, Pemanfaatan TI, Kesesuaian Tugas, dan Keahlian Pemakai Komputer pada Kinerja Karyawan - Anjani Dewantari, Ni Made Fikiyaya; Putra, I Made Pande Dwiana (E-Jurnal Akuntansi; Vol 27 No 1 (2019), 2019)
The purpose of this study is to determine the effect of the effectiveness of the application of accounting information systems, utilization of information technology, suitability of tasks and computer user expertise on employee performance. This research was conducted at PT Karya Luhur Permai Denpasar. Based on the results of the study, it was stated that the effectiveness of the application of accounting information systems, utilization of information technology, suitability of tasks and computer user expertise had a positive and significant effect on employee performance. This means that the higher the effectiveness of the application of accounting information systems, the use of information technology, the suitability of tasks and expertise of computer users, to eat employee performance will increase. This research has proven that the effectiveness of the application of accounting information systems, the use of technology, the suitability of tasks and computer user expertise has a positive influence on employee performance, so it strongly supports the concepts of TAM, TPC Theory, and Contingency Theory. Keywords: Accounting information system, computer user expertise, employee performance